SOYBEAN BRAN AS THE FAT REPLACER IN GLUTEN-FREE COOKIE FORMULATION: PHYSICOCHEMICAL PROPERTIES AND SENSORY PROFILES: Original scientific paper - Milićević, Nataša; Sakač, Marijana; Šarić, Bojana; Škrobot, Dubravka; Filipčev, Bojana; Šimurina, Olivera; Jovanov, Pavle; Pestorić, Mladenka; Marić, Aleksandar (Chemical Industry & Chemical Engineering Quarterly, 2023)
Soybean bran (SB) partially replaced fat (30%—50%) in a gluten-free cookie formulation. Dough properties, physical (cookie dimension and weight loss), textural (hardness and fracturability), colour and sensory parameters, as well as nutritional profiles were evaluated to characterize full-fat (FFC) and fat-reduced cookies (FRC). Based on the obtained results, it was concluded that the fat reduction in cookie formulation at 30% maintained the sensory properties of the FFC. Furthermore, it was revealed that the fat replacement using SB at 30% resulted in the fat-reduced value-added gluten-free cookies in terms of dietary fibre and minerals. A daily portion of the 30% FRC meets 11.87% and 18.04% of dietary reference intakes (DRIs) for dietary fibres, 26.50% of DRIs for calcium, 35.71% and 46.88% of DRIs for magnesium and 65.43% and 83.61% of DRIs for manganese, for male and female adults, respectively.